Risk Management with Supply Contracts - Almeida, Heitor; Hankins, Kristine Watson; Williams, Ryan (Review of Financial Studies, 2017)
Purchase obligations are forward contracts with suppliers and are used more broadly than traded commodity derivatives. This paper is the first to document that these contracts are a risk management tool and have a material impact on corporate hedging activity. Firms that expand their risk management options following the introduction of steel futures contracts substitute financial hedging for purchase obligations. Contracting frictions, such as bargaining power and settlement risk, as well as potential hold-up issues associated with relationship-specific investment, affect the use of purchase obligations in the cross-section, as well as how firms respond to the introduction of steel futures.